Chemical composition, in vitro and in-sacco degradability of dry matter of APBN1 - Panneerselvam, Senthilkumar; Yerradoddi, Ramana Reddy; Suddala, Ramesh; Devanaboyina, Nagalakshmi (Buffalo Bulletin, 2020)
Andhra Pradesh Bajra Napier1 (APBN1) variety of hybrid napier was evaluated for its fodder quality traits using chemical, in vitro and in-sacco techniques. OM, CP, EE, total carbohydrates and TA content of APBN1 variety of hybrid napier were 89.38, 14.98, 2.58, 16.17 and 10.62%, respectively on DM basis. Fiber fractions, NDF, ADF, hemi cellulose, cellulose, lignin and silica content were 68.8, 36.2, 32.6, 29.9, 5.7 and 0.63%, respectively. The calcium, phosphorus, content were 0.09, 0.7%, respectively and the trace element, iron, Zinc and molybdenum content in APBN1 were 341.76, 106.38 and 538.51 ppm, respectively. The IVDMD value of APBN1 was 61.4%, when incubated with buffalo rumen liquor. In-sacco studies revealed that the effective degradable DM (EDDM) and protein of APBN1 variety of hybrid napier was 57.8 and 34.0%, respectively. This study concluded that APBN1 could be used as a good roughage and alternative to existing green fodders for ruminants.